2016
DOI: 10.1021/acs.accounts.6b00445
|View full text |Cite
|
Sign up to set email alerts
|

Flow-Directed Crystallization for Printed Electronics

Abstract: The solution printability of organic semiconductors (OSCs) represents a distinct advantage for materials processing, enabling low-cost, high-throughput, and energy-efficient manufacturing with new form factors that are flexible, stretchable, and transparent. While the electronic performance of OSCs is not comparable to that of crystalline silicon, the solution processability of OSCs allows them to complement silicon by tackling challenging aspects for conventional photolithography, such as large-area electroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
90
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(95 citation statements)
references
References 53 publications
5
90
0
Order By: Relevance
“…These results demonstrate the effectiveness of the solution technique in producing highly oriented polycrystalline films of (diC 8 BTBT)(F n TCNQ) [ n = 0, 2, 4]. The orientation preference should be primarily attributed to the flow‐directed crystallization through the solution‐shearing technique that may have a strong preference for crystal growth along the donor–acceptor stacking axes.…”
Section: Extracted Electron Mobility In Solution‐coated (Dic8btbt)(fnmentioning
confidence: 72%
“…These results demonstrate the effectiveness of the solution technique in producing highly oriented polycrystalline films of (diC 8 BTBT)(F n TCNQ) [ n = 0, 2, 4]. The orientation preference should be primarily attributed to the flow‐directed crystallization through the solution‐shearing technique that may have a strong preference for crystal growth along the donor–acceptor stacking axes.…”
Section: Extracted Electron Mobility In Solution‐coated (Dic8btbt)(fnmentioning
confidence: 72%
“…On isotropic substrates, the crystallization of molecular materials typically results in fibre-textured films comprising crystallites that share a common fibre axis perpendicular to the substrate surface but are azimuthally randomly oriented (Witte & Wö ll, 2004). The use of anisotropic substrates (like rubbed polymer surfaces or single-crystalline surfaces) or anisotropic preparation methods (like off-centre spin coating, dip coating or off-axis evaporation) can result in even more distinguished textures of the crystallites (Mü ller et al, 1999;Brinkmann et al, 2003;Qu et al, 2016). In this context, particularly complicated cases include epitaxially grown molecular crystals on singlecrystalline surfaces (Simbrunner et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Solution processible organic semiconductors (OSCs) offer great opportunities for low‐cost and large‐area manufacturing of flexible electronics . Morphology control is crucial to achieving high‐performance devices and to elucidating the complex structure–charge transport property relationship . Morphology is shown to be highly sensitive to processing conditions, such as printing/coating speed, solvent choices, substrate chemistry and topology, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Morphology control is crucial to achieving high-performance devices and to elucidating the complex structure-charge transport property relationship. [5][6][7] Morphology is shown to be highly sensitive to processing conditions, 8 such as printing/coating speed, 3,[9][10][11] solvent choices, 12,13 substrate chemistry and topology, 14,15 and so on. It has been widely shown that morphological parameters can modulate charge carrier mobility by orders of magnitude.…”
mentioning
confidence: 99%